Falling hospital and postdischarge mortality following CABG in New South Wales from 2000 to 2013 - Karice Hyun; David B Brieger; Austin C C Ng; Vincent Chow; Mario D'Souza; Paul G Bannon; Leonard Kritharides (Open Heart)
Objectives To describe changes in mortality among patients undergoing coronary artery bypass grafting (CABG) in New South Wales (NSW) Australia from 2000 to 2013.Methods Patients undergoing CABG were identified from the NSW Admission Patient Data Collection (APDC) registry, linked to the NSW state-wide death registry database. Changes in all-cause mortality over time were observed following stratification of the study cohort into two year groups.Results We identified 54 767 patients undergoing CABG during the study period. The risk profile of patients increased over time with significant increases in age, comorbidities and concomitant valve surgery (all p < 0.0001). During a median follow-up period of 6 years, a total 12 161 (22.2%) of patients had died. Survival curves and adjusted analyses showed a steady fall in mortality rate: those operated on during 2012–2013 had 40 % lower mortality than those operated on during 2000–2001 (HR 0.61; 95% CI 0.53 to 0.69). This was contributed to both by a fall in mortality both in hospital (HR 0.48, 95% CI 0.37 to 0.62) and postdischarge (HR 0.73; 95% CI 0.61 to 0.86).Conclusions We report a consistent reduction in medium-term mortality among a large unselected cohort of NSW patients undergoing CABG between 2000 and 2013. This fall is attributable both to an improvement in outcomes in hospital and in the postdischarge period.